A Study of Alkaline-Based H2-Br2 and H2-I2 Reversible Fuel Cells. Issue 14 (20th October 2016) - Dowd, Regis P.; Yarlagadda, Venkata; Konwar, Dhrubajit; Lin, Guangyu; Weng, Guoming; Li, Chi-Ying Vanessa; Chan, Kwong-Yu; Van Nguyen, Trung
Abstract : The hydrogen-bromine (H2 -Br2 ) and hydrogen-iodine (H2 -I2 ) reversible fuel cell systems can be operated in the acid or alkaline modes. The alkaline versions were evaluated because of the advantages over the acidic systems such as higher cell potential, lower corrosivity, and lower catalyst cost for the hydrogen evolution and oxidation reactions. Fuel cells were assembled to validate the operational feasibility of the alkaline systems and to evaluate their performance. The results confirmed that the alkaline H2 -Br2 and H2 -I2 fuel cells have a higher cell voltage than their corresponding acidic systems while maintaining similarly fast electrode reaction kinetics. However, the performance of these alkaline fuel cells is currently limited by the low ionic conductivity of the K + form membranes, which is attributed to the slow diffusivity of the larger K + ion in these membranes, and providing equal access of gaseous and liquid reactants to the active sites for the hydrogen reaction. These limitations could be overcome by using thinner membranes, operating the fuel cell at higher concentrations and temperatures, and development of porous electrodes with better two-phase fluid distribution.